Recent Advances in Plant Biotechnology and Genetic Engineering: Application in Agriculture - Fatima, Mahpara; Zaynab, Madiha; Sharif, Yasir; Abbas, Safdar; Zaffar, Muhammad Hammad; Saleem, Tahira (International Journal of Molecular Microbiology, 2018)
Increasing population is facing the challenge for food security. Researchers are searching the convenient and fast ways for improving crop production. Basic research provides us with genetic mechanism of plants. Tools have been discovered to manipulate and alter these mechanisms to get the new and desirable products and to incorporate innovative characteristics in plants. Synthetically made promoters, enhancers and repressors for native or transgene expression regulation are some of these tools. Some tools like, transformation of plant with artificially synthesized chromosomes and linked multiple genes are gaining importance. The most advanced one is CRISPR-Cas genome editing system. To assess their implicational potential in addressing agro-environmental problems, such genomic tools should be integrated.